Therapeutic Potential of Eugenol for Muscle Pain Management in Athletes: A Scoping Review - Mochtar, Chaerul Fadly (Journal of Basic Medical Veterinary, 2025)
Muscle pain is a prevalent affliction experienced by athletes during training and competition. Eugenol, a natural compound found in cloves, exhibits considerable promise as a therapeutic agent for myalgia through multiple mechanisms of action. Eugenol has been shown to inhibit prostaglandin E2 production and reduce cyclooxygenase-2 (COX-2) expression, a process that plays a pivotal role in inflammation and pain. Furthermore, eugenol has been observed to interact with TRPV1, HVACC, and α2-adrenergic and opioidergic receptors, contributing to its analgesic effects. In addition, studies have demonstrated that eugenol possesses significant anti-inflammatory properties, as evidenced by its ability to reduce the expression of pro-inflammatory cytokines and augment the activity of antioxidant enzymes. In a preclinical context, eugenol-active topical formulations have demonstrated encouraging results, showing promise in the development of muscle pain relief preparations for athletes, with a superior safety profile compared to conventional drugs. However, further research is necessary to optimize the dosage, formulation, and the appropriate application method. This review underscores the potential of eugenol as a safe and effective muscle pain therapy for athletes, as well as opportunities for the development of innovative topical formulations.